Inhalable liposomes of Glycyrrhiza glabra extract for use in tuberculosis: formulation, in vitro characterization, in vivo lung deposition, and in vivo pharmacodynamic studies. (2nd January 2019) - Viswanathan, Vivek; Pharande, Rajesh; Bannalikar, Anilkumar; Gupta, Pushpa; Gupta, Umesh; Mukne, Alka
Abstract: Objective: The current study involves the development of liposomal dry powder for inhalation (LDPI) containing licorice extract (LE) for use in tuberculosis. Significance: The current epidemiology of tuberculosis along with the increasing emergence of resistant forms of tuberculosis necessitates the need for developing alternative efficacious medicines for treatment. Licorice is a medicinal herb with reported activity against Mycobacterium tuberculosis . Methods: Liposomes with LE were prepared by thin film hydration technique and freeze dried to obtain LDPI. The comprehensive in vitro and in vivo characterization of the LDPI formulation was carried out. Results: The particle size of liposomes was around 210 nm with drug entrapment of almost 75%. Transmission electron microscopy revealed spherical shape of liposome vesicles. The flow properties of the LDPI were within acceptable limits. Anderson Cascade Impactor studies showed the mean median aerodynamic diameter, geometric standard deviation and fine particle fraction of the LDPI to be 4.29 µm, 1.23, and 54.68%, respectively. In vivo lung deposition studies of LDPI in mice showed that almost 46% of the drug administered reaches the lungs and 16% of administered drug is retained in the lungs after 24 hours of administration. The in vivo pharmacodynamic evaluation of the LDPI showed significant reduction in bacterial counts in lungs as well as spleen of TB-infected mice. Conclusions: LE LDPI thus has a promising potential to be explored as an effective anti-tubercular medicine or as an adjunct to existing anti-tubercular drugs.